Penerapan Metode Electre Dalam Pemilihan Kepala Biarawati - Gule, Senima; Ginting, Guidio Leonarde; Sihite, Anggiat M Hatuaon (JURIKOM (Jurnal Riset Komputer), 2020)
In the election of the head of a nun, usually a nun who will be elected as head must be a nun who has been educated for ten years, and has been legalized as eternal vows, and meets the age of over thirty years, and six years after her eternal vows, the nun can only elected to be a head, and usually in a manual way, namely through voting the most votes, the right to become chairman is the most votes, this manual system is actually not wrong, but if the system in selecting the head of a nun that uses the manual system is not correct, Because it takes a long time to determine, vote count errors often arise, and the head of the nun who is elected as a result of the calculation process is not based on predetermined criteria, then with the new system, the election does not only use the most votes but also through the k-criteria. The riteria that has been determined in the system will get faster and more precise results in the election of the head of a nun, of course, supported by the diocesan council as the final decision maker.Therefore, to facilitate the election, you can use the Electre method which is also computerized to get better results. The Electre method (Elimination Et Choix Traduisant La Realite) is one of the methods in the Multi Criteria Decision Making (MCDM) which is based on the outranking concept using paired comparisons of the alternatives for each suitable criterion. Although it does not guarantee its efficiency, using this method can help decision makers make decisions more accurately in the selection of the Head of Nuns.